Identity of vertebrate diversity in Langsa City Forest Park - Annisa Syabrina; Aura Alfisyahrin; Cut Anisa Khairani; Diah Khairani; Jeli Parsela; Syasya Salbila; Ayu Wahyuni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Vertebrates is a type of animal that has a spine or backbone. Vertebrates are members of the phylum chordata and are bilateral animals (bilateral symmetry).This research aims to identify vertebrate species in the Langsa City Protected Forest which functions as ecotourism. In this research, the Exploration method using direct observation in the field has been analyzed descriptively. The research produced data that there were 22 vertebrate species in the Langsa City Protected Forest. Of the 22 species of vertebrates that are most protected in captivity, there are 3 species from the Acciptriformes order, 3 species from the Artiodactyla order. The results of this study are expected to provide information on the diversity of Vertebrata in the area of Langsa City Protected Forest that is used as an ecosystem.